2008
DOI: 10.1051/ijsmdo:2008028
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling of abradable materials – Identification of plastic parameters and issues on minimum hardness against coating's thickness

Abstract: -Abradable materials are used to decrease the gas consumption of aircraft engines by minimizing the gap between the blade tips and the stator. The key idea consists in using the blades themselves to machine the gap on the abradable coating. The best compromise between soft and hard coating properties has to be reached to avoid blades wear and prevent coating erosion by gas flux and particles. The plastic parameters of abradable coating were identified by using an optimization process directly connected to FEA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…If the experimental static characterization of this material [16,17] is known, the dynamic characterization is still being investigated [18]. For instance, the finite element method combined with an optimization procedure is employed in [19] for the simulation of the HR15Y hardness test on abradable material. It was shown that a bilinear plastic law could accurately represent the mechanical behavior of abradable material.…”
Section: Introductionmentioning
confidence: 99%
“…If the experimental static characterization of this material [16,17] is known, the dynamic characterization is still being investigated [18]. For instance, the finite element method combined with an optimization procedure is employed in [19] for the simulation of the HR15Y hardness test on abradable material. It was shown that a bilinear plastic law could accurately represent the mechanical behavior of abradable material.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better estimate the wear parameter, comparisons with experimental results such as the ones presented in [14,15] have to be scheduled in a near future. Other approaches in the form of frequency-domain formulated nonlinear normal modes may be relevant for faster parameter studies [8].…”
Section: Resultsmentioning
confidence: 99%
“…L'identification expérimentale de ces matériaux est sujet de nombreuses études [5] mais leur modélisation dans des configurations réalistes semble limitée.…”
Section: Introductionunclassified